Epistemologies and the Limitations of Philosophical Inquiry : Doctrine in Màdhva Vedanta. - Clooney, Francis X. (Francis Xavier), 1950- (RoutledgeCurzon, 2004)
Deepak Sarma explores the degree to which outsiders can understand and interpret the doctrine of the Màdhva school of Vedànta.